The importance of pharmaceutical guidance at hospital discharge and in the post-discharge self-care process: an integrative review (Research, Society and Development, 2022)
This research aims to address pharmaceutical guidance at hospital discharge since in the discharge process, in the transition from hospitalization to self-care, where the patient is vulnerable, medication reconciliation and effective communication between the team and the patient are extremely important. Methods: An integrative literature review carried out in the Virtual Health Library (BVS) and Pubmed databases, using the domains “patient safety”, “hospital discharge” and “medication reconciliation”. Publications were selected according to inclusion and exclusion criteria; the analysis of the articles was done by pairs; Languages: English and Portuguese. The search in the databases resulted in 13 studies. For data processing and analysis, the IRAMUTEC software and the application of the URSI form were used. Results: The present RIL has a good level of scientific evidence, helping to expand knowledge on the subject. The Descending Hierarchical Classification (CHD) identified three semantic classes according to the analysis of textual domains and interpretation of meanings: 1- Changes and therapeutic changes as the main cause of damage and adverse events after hospital discharge; 2- Health education and medication guidance as a stimulus to self-care after hospital discharge; 3- Information and home monitoring to improve the problem regarding the use of medications after hospital discharge. Conclusion: The present review made it possible to clarify the importance of the pharmacist in the discharge orientation and how he can intervene in the self-care process, even though his role is not well defined.